Clinical and genetic characteristics of Chinese Duchenne/Becker muscular dystrophy patients with small mutations - Gan, Siyi; Liu, Shulei; Yang, Haiyan; Wu, Liwen (Frontiers in Neuroscience, 2022)
Background: Duchenne/Becker muscular dystrophy (DMD/BMD) are amongst the inherited neuromuscular diseases with the highest incidence. Small mutations are less common and therefore have been poorly studied in China. Methods: The clinical data of 150 patients diagnosed with DMD/BMD by genetic analysis in Hunan Children's Hospital from 2009 to 2021 were analyzed. The patients were followed up for an average of 3.42 years and their clinical characteristics were collected. Loss of ambulation (LOA) was used to evaluate the severity of disease progression. The correlation among clinical features, different variants and glucocorticoid (GC) treatment was analyzed by Cox regression analysis. Results: 150 different variants were detected in this study, including 21 (14%) novel mutations, 88 (58.7%) nonsense mutations, 33 (22.0%) frameshift mutations, 22 (14.7%) splicing mutations, and 7 (4.7%) missense mutations. Single-exon skipping and single- or double-exon (double/single-exon) skipping strategies covered more than 90% of patients with small mutations. A case with frameshift mutation combined with Klinefelter's syndrome (47, XXY) and another one with missense mutation combined with epilepsy was found in our study. De novo mutations accounted for 30.0% of all patients. The mean onset age was 4.19±1.63 years old, and the mean diagnosed age was 5.60±3.13 years old. The mean age of LOA was 10.4 years old (40 cases). 60.7% of them received GC treatment at 7.0±2.7 years old. The main causes of complaints were muscle weakness, high creatine kinase (CK), motor retardation and family history. The risk factors of LOA were positive family history (HR 5.52, CI 1.26 to 24.18), short GC treatment duration and frameshift mutation. DMD patients who treated with GC after 7 years old had a higher risk of earlier LOA compared to those receiving treatment before the age of 7. Moreover, an earlier onset age, a higher CK value, and a larger LOA population were found in the DMD patients compared to the BMD ones. Finally, the locations of the most frequent mutation were in exon 70 and exon 22. Conclusion: In conclusion,our findings complement the mutation spectrum of DMD/BMD, benefit us understanding to the DMD disease, and lay foundations for the clinical trials.